AuCo nanoparticles: ordering, magnetisation, and morphology trends predicted by DFT. Issue 17 (20th April 2022) - Farkaš, Barbara; de Leeuw, Nora H.
Abstract : Structure-driven evolution of magnetic behaviour of AuCo nanoparticles showcases efficacy of the elementary intermixing in enhancing magnetisation and magnetic anisotropy. Abstract : The rapid development of applications relying on magnetism at the nanoscale has put a spotlight on nanoparticles with novel morphologies that are associated with enhanced electronic and magnetic properties. In this quest, nanoalloys combining highly magnetic cobalt and weakly reactive gold could offer many application-specific advantages, such as strong magnetic anisotropy. In the present study, we have employed density functional theory (DFT) calculations to provide a systematic overview of the size- and morphology-dependence of the energetic order and magnetic properties of AuCo nanoparticles up to 2.5 nm in diameter. The core–shell icosahedron was captured as the most favourable morphology, showing a small preference over the core–shell decahedron. However, the magnetic properties (total magnetic moments and magnetic anisotropy) were found to be significantly improved within the L10 ordered structures, even in comparison to monometallic Co nanoparticles. Atom-resolved charges and orbital moments accessed through the DFT analysis of the electronic level properties permitted insight into the close interrelation between the AuCo nanoparticle morphology and their magnetism. These results are expected to assist in the design of tailored magnetic AuCo nanoalloys for specific applications.